Investigating KIF1A mutations in a Taiwanese cohort with hereditary spastic paraplegia. (October 2022) - Hsu, Shao-Lun; Liao, Yi-Chu; Lin, Kon-Ping; Lin, Po-Yu; Yu, Kai-Wei; Tsai, Yu-Shuen; Guo, Yuh-Cherng; Lee, Yi-Chung
Abstract: Background: Hereditary spastic paraplegia (HSP) is a heterogeneous group of inherited neurodegenerative disorders characterized by slowly progressive lower limbs spasticity and weakness. HSP type 30 (SPG30) is a HSP subtype caused by mutations in the kinesin family member 1A gene ( KIF1A ) and could be either autosomal dominantly or recessively inherited. The aim of this study was to investigate the clinical and genetic features of KIF1A mutations in a Taiwanese HSP cohort. Methods: Mutational analysis of KIF1A was performed in 242 unrelated Taiwanese patients of Han Chinese ethnicity with clinically suspected HSP using targeted resequencing panel covering the entire coding regions of KIF1A . Clinical, electrophysiological and neuroimaging features of the HSP patients carrying a KIF1A mutation were characterized. Results: Three different KIF1A mutations were identified in three patients with autosomal dominantly inherited HSP. Among them, KIF1A p.E19K was a novel mutation. The patient harboring KIF1A p.G321D presented with pure HSP, while the individuals carrying KIF1A p.E19K or p.R316Q manifested complex HSP with additional axonal sensorimotor polyneuropathy. The patients carrying KIF1A p.R316Q also had thoracic cord atrophy, thin corpus callosum and white matter hyperintensity. Conclusion: SPG30 accounts for 1.2% (3/242) of patients in the Taiwanese HSP cohort, suggesting that it is an uncommon HSP subtype in Taiwan. This study delineates the clinical and genetic features of SPG30 in Taiwan and provides useful information for the diagnosis and management of SPG30, especially in patients of Han Chinese descent. Highlights: KIF1A mutations account for 1.2% (3/242) of the patients with HSP phenotype in Taiwan. The KIF1A p.E19K is a novel mutation for SPG30. SPG30 patients may manifest pure HSP or complex HSP. Polyneuropathy may serve as a clue for diagnosing SPG30.